Disparities in prices and income across German NUTS 3 regions - Reinhold Kosfeld; Hans-Friedrich Eckey; Jørgen Lauridsen (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2007)
In EU countries, knowledge on spatial disparities in overall price level is extremely scarce. When interregional price disparities are large, however, nominal income measures fail to assess prosperity and the catch-up processes of regions. Despite its importance for regional policy, no official regional price statistic is available as a standard. On account of this gap, this paper deals with the econometric estimation of regional price indices for German NUTS 3 regions. Econometric price models for the consumer price index (CPI) and the housing rent index (HRI) are developed on the ground of utility maximization in a two-goods model. The estimated price indices are used to analyse price disparities in the period 1995-2004 across German NUTS 3 regions. Real income comparisons show that the East/West gap is likely to be substantially larger than assessed from incomplete price data in previous studies.
Keywords: C21; R13; R31; 330; Regional price level; econometric price models; price disparities; real income disparities; Regionale Preisstruktur; Regionale Disparität; Regionale Entwicklung; Volkseinkommen; Deutschland